I MUSEI DELLA SCIENZA - Salvemini, Francesca (Archeomatica, 2012)
Nell'iconologia umanistica di artisti che hanno fondato l'illustrazione enciclopedica alla base della nostra epistemologia gli strumenti astronomici delle scienze della Terra. The museums of science - In humanistic iconology of artists who founded the encyclopedic illustration at the base of our epistemology the astronomical instruments of the earth sciences. The author retraces iconographic elements that have had earth sciences at primary subject with a particular repertoire of artists that intersect with each other to form the primary link between art and science that are now the basis of our knowledge.